Validity and Reliability Test of the Indonesian Version of the Niigata Persistent Postural-Perceptual Dizziness Questionnaire (NPQ-Ina) - Siregar, Desmita; Ariarini, Ni Nengah Rida; Sitorus, Freddy; Budikayanti, Astri; Diafiri, Dinda; Indrawati, Luh Ari (Acta Neurologica Indonesia, 2026)
Introduction : Postural Persistent Perceptual Dizziness (PPPD) is the most common disorder among chronic-onset nd vestibular syndromes, accounting for 37% of cases, characterized by persistent dizziness, unsteadiness, anon-spinning vertigo exacerbated by movement, visual stimuli, and upright posture. The Niigata PPPD Questionnaire (NPQ) assesses these domains, but an Indonesian version has not been validated. Objective : To conduct cross-cultural adaptation and evaluate the validity and reliability of the Indonesian version (NPQ-Ina). Material and methods : This analytical cross-sectional study included adults diagnosed with chronic-onset vestibular disorders based on ICVD criteria at the Neurology Outpatient Clinic of Dr. Cipto Mangunkusumo National General Hospital. Cross cultural adaptation followed WHO guidelines. Construct validity was assessed using item total correlation, and internal consistency reliability was evaluated using Cronbach’s alpha. Result : Of the 36 study participants, the majority were female (91.7%) with a mean age of 52.2 ± 10.5 years, a median symptom duration of 19.5 months, and the most common diagnosis was PPPD (47.2%). All NPQ-Ina items showed significant and strong item-total correlations (0.617–0.875). The overall Cronbach’s alpha was 0.894. The visual and postural factors demonstrated high reliability (α = 0.818 and 0.815), while the movement factor showed moderate reliability (α = 0.685). Discussion : Strong validity and reliability across domains support the conceptual integrity of the NPQ-Ina, while slightly lower reliability in the movement factor may reflect diagnostic heterogeneity. Conclusion : The NPQ-Ina is a valid and reliable instrument for assessing symptom exacerbating factors in chronic onset vestibular disorders in the Indonesian population.